2020
DOI: 10.1016/j.cognition.2020.104193
|View full text |Cite
|
Sign up to set email alerts
|

Physically attractive faces attract us physically

Abstract: When interacting with other humans, facial expressions provide valuable information for approach or avoid decisions. Here, we consider facial attractiveness as another important dimension upon which approach-avoidance behaviours may be based. In Experiments 1-3, we measured participants' responses to attractive and unattractive women's faces in an approach-avoidance paradigm in which there was no explicit instruction to evaluate facial attractiveness or any other stimulus attribute. Attractive faces were selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 40 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…Rather, the automatic emotional appraisal we attribute to objects, derived from our past experiences with them, influences the actions we make toward them. For example, we more readily approach positive objects and tend to avoid negative objects ( Chen and Bargh, 1999 ; Kramer et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rather, the automatic emotional appraisal we attribute to objects, derived from our past experiences with them, influences the actions we make toward them. For example, we more readily approach positive objects and tend to avoid negative objects ( Chen and Bargh, 1999 ; Kramer et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This model (approachability, youthful-attractiveness, and dominance) appears to better approximate how real faces are socially evaluated, and in contrast to PCA-derived solutions (which are orthogonal by definition), it captures correlations in underlying structure. For example, the youthful-attractiveness factor correlates with the approachability factor, mirroring how attractive faces induce approach behaviours in observers (Kramer et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…P1 is considered to be the reflection of the early stage of face processing, the rough facial representation and the retrieval of the simple facial features ( Itier and Taylor, 2004 ; Kranz and Ishai, 2006 ). A study employed real and virtual faces to compare the processing differences between sad and neutral facial expressions and found that sad expressions cause stronger P1 than neutral expressions within a time window of 80 ~ 110 ms ( Kramer et al, 2020 ). In attention-oriented research, P1 is often considered to be related to early attention and low-level physical classification of stimuli ( Itier et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with young American females, who pay more attention to body shape, Asian females, especially Chinese young females, believe that beautiful faces are more important ( Chen and Jackson, 2005 ; Chen et al, 2006 ; Hua, 2009 ; Luo, 2013 ). Highly attractive (HA) pictures are considered to be more advantageous for health ( Shackelford and Larsen, 1999 ; Henderson and Anglin, 2003 ; Little et al, 2011 ), spouse selection ( McNulty et al, 2008 ; Ma-Kellams et al, 2017 ; Arnocky, 2018 ), career trajectory ( Halford and Hsu, 2020 ), and decision-making ( Kowner, 1996 ; Chen et al, 2012 ; Atari et al, 2017 ; Kramer et al, 2020 ). Chen and colleagues’ research on physical dissatisfaction among Chinese adolescents found that facial appearance is one of the main sources of negative body images among Chinese female adolescents, and dissatisfaction with facial appearance is one of the most important predictors of negative physical self-image among young females.…”
Section: Introductionmentioning
confidence: 99%